2018
DOI: 10.1038/s41467-018-06404-w
|View full text |Cite|
|
Sign up to set email alerts
|

LOTUS domain protein MARF1 binds CCR4-NOT deadenylase complex to post-transcriptionally regulate gene expression in oocytes

Abstract: Post-transcriptional regulation of gene expression plays an essential role during oocyte maturation. Here we report that Drosophila MARF1 (Meiosis Regulator And mRNA Stability Factor 1), which consists of one RNA-recognition motif and six tandem LOTUS domains with unknown molecular function, is essential for oocyte maturation. When tethered to a reporter mRNA, MARF1 post-transcriptionally silences reporter expression by shortening reporter mRNA poly-A tail length and thereby reducing reporter protein level. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 59 publications
1
42
1
Order By: Relevance
“…nos may not be the only target of dMarf1; other mRNAs such as tra2 and abo can also be targeted by dMarf1, although the biological significance of these interactions remains unclear. Zhu et al have recently reported that dMarf1 can bind to cyclin A mRNA via its RRM domain [8]. However, our RNA-IP analysis did not detect cyclin A in the dMarf1-bound mRNA fraction (S4 Table).…”
Section: Plos Onecontrasting
confidence: 56%
See 3 more Smart Citations
“…nos may not be the only target of dMarf1; other mRNAs such as tra2 and abo can also be targeted by dMarf1, although the biological significance of these interactions remains unclear. Zhu et al have recently reported that dMarf1 can bind to cyclin A mRNA via its RRM domain [8]. However, our RNA-IP analysis did not detect cyclin A in the dMarf1-bound mRNA fraction (S4 Table).…”
Section: Plos Onecontrasting
confidence: 56%
“…The C-terminal region of the MARF1 family members is highly conserved among higher animals, except insects (S3 and S4 Figs), despite not forming any secondary structure. The Cterminal region of human MARF1 has been shown to directly interact with the decapping complex component Ge-1 [21]; however, this interaction was not observed in Drosophila [8]. Moreover, the C-terminal region of the MARF1 family members is conserved among different insect species, but different from that of higher animals (S4 Fig), indicating that it may bind to a unique partner in insects.…”
Section: Plos Onementioning
confidence: 98%
See 2 more Smart Citations
“…True NYN proteins also include Limkain enzymes, such as MARF1 in animals and MNU1 and MNU2 in plants (Table ). MARF1 is localized in P‐bodies where it interacts with components of the decapping complex and in Drosophila can recruit the CCR4‐NOT deadenylase complex . While MARF1 enzymes always occur in animals, their overall structure varies.…”
Section: Introductionmentioning
confidence: 99%